Realimentação derivativa e modelo fuzzy Takagi-Sugeno paracontrole da articulação do joelho de pacientes paraplégicos com o uso de acelerômetros - Gaino, Ruberlei; Teixeira, Marcelo Carvalho Minhoto [UNESP]; de Carvalho, Aparecido Augusto [UNESP]; Assunção, Edvaldo [UNESP]; Cardim, Rodrigo [UNESP]; Sanches, Marcelo Augusto Assunção [UNESP]; Covacic, Márcio Roberto (Editora Cubo, 2011)
Feedback control systems have been used to move the muscles and joints of the limbs of paraplegic patients. The feedback signal, related to the knee joint angle, can be obtained by using an electrogoniometer. However, the use of accelerometers can help the measurements due the facility of adhering these devices to the skin. Accelerometers are also very suitable for these applications due their small dimensions and weight. In this paper a new method for designing a control system that can vary the knee joint angle using Functional Electrical Stimulation (FES) is presented, as well as a simulation with parameters values available in the literature. The nonlinear control system was represented by a Takagi-Sugeno fuzzy model and the feedback signals were obtained by using accelerometers. The design method considered all plant nonlinearities and was efficient and reliable to control the leg position of a paraplegic patient with the angle of the knee ranging from 0° to 30°, considering electric stimulation at the quadriceps muscle. The proposed method is viable and offers a new alternative for designing control systems of the knee joint angle using more comfortable sensors for the patients.
Derivative feedback and Takagi-Sugeno fuzzy model for knee joint angle control of paraplegic patients using accelerometers
Keywords: Accelerometers; Functional electrical stimulation; Nonlinear control; Takagi-sugeno fuzzy; Derivative feedbacks; Design method; Designing control system; Electric stimulation; Electrogoniometers; Feedback signal; Knee-joint angle; Non linear control; Paraplegic patients; Takagi Sugeno fuzzy models; Takagi-sugeno; Adaptive control systems; Control nonlinearities; Electrophysiology; Electrotherapeutics; Feedback control; Functional electric stimulation; Muscle; Nonlinear feedback; Well stimulation; Joints (anatomy)